Analysis of the Use of the Veil for Students of the Islamic Faculty of Universitas Muhammadiyah Sumatera Utara - Khairunnisa Khairunnisa; Anggie Veronica; Siti Windya Antika (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
This research was conducted to examine the problems regarding the use of the veil in the Universitas Muhammadiyah Sumatera Utara, especially in the Faculty of Islamic Religion. Regarding the technical information retrieval, the authors sent questionnaire data to individuals related to the research.Â Based on the results of the study, there are many things behind female students in using the veil. That is based on the Qur'an surah Al Ahzab verse 59 Allah SWT. said that it is obligatory for Muslim women to extend the veil over their bodies to avoid the fitna of the world and they also interpret the veil as a safeguard against themselves. Regarding the use of this veil, not a few agencies stand on the contra side. Especially on campus.Â At the Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, students who wear the niqab are advised not to wear the veil when they are on campus. This is based on the context of Muhammadiyah which argues that there is no recommendation for Muslim women to wear the veil. Because of this statement, veil users feel that they are limited in carrying out activities in the campus environment.